Optimalisasi Peran Guru Pendidikan Agama Islam Dalam Menggunakan Masjid Untuk Meningkatkan Mutu Pelajaran Fiqih Ibadah Di Smp Muhammadiyah 1 Surakarta Tahun Pelajaran 2015/2016 - Noviyani, Rafiqa (2016)
Mosque as the infrastructure can be used as supporting subject of Jurisprudence of Worship. The purposes of the subjects Jurisprudence of Worship are practice and carrying out the provisions of Islam correctly in implementing worship to Him. For the realization of these objectives, the role of teachers in learning is needed. Teacher as a spearhead in the learning process, which is in direct contact with students has a large stake in order to achieve the goal of Worship Fiqih both in terms of cognitive, affective and psychomotor. On the subjects of Jurisprudence of Worship, teachers cannot give the material only on the cognitive side. Therefore it takes practice and habitation through the means that provided in school, that is the mosque. This study examines the "Optimization of the Role of Islamic Religious Education Teachers in Using Mosques to Improve The Quality of Jurisprudence of Worship Subject in Muhammadiyah 1 Senior High School of Surakarta in 2015/2016 Academic Year. This research is a field research with descriptive qualitative approach and methods of data analysis by the inductive method, namely data reduction, data presentation, and conclusion. The results of this study show that a mosque be a means that is positive in improving the quality of teaching Jurisprudence of Worship which is obtained through the teacher's role, namely: (1) teacher acts as an educator / demonstrator with the aim that students always get a source of knowledge and can be modeled with a demonstration of teachers, ( 2) teacher acts as a mentor with the aim to familiarize students worship properly through practice, (3) the teacher acts as a facilitator with the goal of providing resources and related facilities, (4) teacher acts as a motivator with a view to foster and improve students' motivation in worship, (5) teacher acts as an evaluator with the aim that students always receive an evaluation to strengthen the understanding of the obtained material. Whereas the constraints faced by teachers are technical constraints, lack of time in learning and two constraint factors are both of teachers and students. Teachers are less participation in practice guiding and students still act passively during the learning process.